Flow measurement methods. - Jusoh, Ahmad (1989)
This lesson will focus on the flow measurement methods that can be used in the field without the installation of a primary device. Methods to be covered include the trajectory method, the California pipe method, velocity meters, velocity and depth measurement, level changes in tanks, and pumping rate determination. Sample problems for each method will be presented.